Analyzing living conditions of Tomsk physicists' scientific community in the period of social and economic upheaval (1930-1945); The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Sorokin A. N. Aleksandr Nikolaevich (2016, 2016)
Title screen